Mechanical spectroscopy to determine the torsion modulus from hollow glass microspheres fillers in unsaturated polyester resin - Pintão, Carlos Alberto Fonzar [UNESP] (2024)
This work presents an alternative to studying and determining the torsion modulus, G, in composites. For this purpose, a measuring system used a rotational motion sensor coupled to a torsion pendulum. The determination of the angular position as a function of time and an equation derived from studies of mechanical spectroscopy, allowed to determine the value of G, so experiments focused on samples of different quantities of hollow glass microspheres (HGMs) in unsaturated polyester resins. The G results show that the addition of HGMs (16.67 %W) reduces the value of torsion modulus by 31% when compared to the unsaturated resin (100 %W). On the other hand, considering the same two samples, there is a material density reduction of approximately 43% with the addition of HGMs, which makes these materials lighter, and of great practical interest. The relationship between G and material density shows that it is possible to change the amount of HGMs for optimal torsion resistance. The advantage of this technique, compared to other dynamic methods, is that it is not necessary to know the Poisson’s ratio of the material.